Hyperferritinemia Correlated with Activated Population of Natural Killer Cells in Pediatric Major β-Thalassemia Patients - Adi Imam Cahyadi; Mohammad Ghozali; Reni Ghrahani; Lelani Reniarti; Ramdan Panigoro (Universitas Islam Bandung, 2021)
Natural killer (NK) cells act both as cytotoxic and cytokine producers in the innate immune response. Hyperferritinemia resulting from a routine blood transfusion as a specific treatment in major β-thalassemia patients may disturb the cellular immune system’s harmony. This study aims to investigate the correlation between hyperferritinemia and the NK cell subsets in major β-thalassemia settings. Pediatric major β-thalassemia patients who routinely received a blood transfusion at Dr. Hasan Sadikin General Hospital in 2016 were included in this cross-sectional study. Blood samples were treated with the monoclonal antibody of CD3, CD56, and CD16 to count the NK cells subsets as CD56bright, CD56dim, and CD16+ using flowcytometry. CD69+ used as an activation marker. The median fluorescence intensity (MFI) of CD56, CD16, and CD69 was measured. Total iron-binding capacity (TiBC), ferritin, and serum iron level examined as iron status. A Spearman correlation test was used for statistical analysis. Fifty-five blood samples were obtained for analysis. This study reveals that the percentage of CD3− lymphocyte population was correlated with the ferritin levels (r=−0.45, p=0.0009). Positive correlation was revealed between activated population (CD69+) of CD56bright and CD56dim NK cell subsets and hyperferritinemia [(r=0.353, p=0.008) and (r=0.355, p=0.008)]. The activated CD56bright cells was associated with ferritin level (r=0.353, p=0.008) and TiBC (r=0.334, p=0.018). Hyperferritinemia in pediatric major β-thalassemia patients may influence NK cell subsets' balance population, particularly the CD56bright and CD56dim NK cell subsets, then alter their immune response to pathogens. KORELASI ANTARA HIPERFERITINEMIA DAN SEL NATURAL KILLER TERAKTIVASI PADA ANAK DENGAN TALASEMIA BETA MAYORSel-sel natural killer (NK) telah diketahui memiliki peran sitotoksik dan dalam produksi sitokin pada respons imun bawaan. Hiperferitinemia merupakan hasil dari transfusi darah rutin yang dijalani sebagai terapi utama pada talasemia mayor. Penelitian ini bertujuan mempelajari hubungan hiperferitinemia dan sel NK pada talasemia beta mayor. Penelitian potong lintang ini melibatkan anak dengan talasemia beta mayor yang secara rutin menerima transfusi darah di RSUP Dr. Hasan Sadikin selama tahun 2016. Sampel darah diberi marker CD3, CD56, dan CD16 untuk menghitung subset sel NK sebagai CD56bright, CD56dim, dan CD16+ menggunakan flowcytometry. CD69+ digunakan sebagai penanda aktivasi. Median fluorescence intensity (MFI) CD56, CD16, dan CD69 diukur. Kadar TiBC, ferritin, dan Fe serum diperiksa sebagai status besi. Uji korelasi Spearman digunakan pada analisis statistik. Analisis dilakukan terhadap 55 sampel darah anak dengan talasemia. Penelitian ini mendapatkan populasi limfosit CD3 berkorelasi dengan kadar feritin (r=−0,45; p=0,0009). Korelasi positif didapatkan pada populasi teraktivasi (CD69+) dari subset sel CD56bright dan CD56dim NK serta hiperferitinemia [(r=0,353; p=0,008) dan (r=0,355; p=0,008)]. Sel CD56bright teraktivasi berkorelasi dengan kadar feritin (r=0,353; p=0,008) dan TiBC (r=0,334; p=0,018). Hiperferitinemia pada anak dengan talasemia mayor dapat memengaruhi populasi sel NK, khususnya pada subset CD56bright dan CD56dim sehingga berpengaruh pada respons imun terhadap patogen.